2006
DOI: 10.1002/ejic.200500731
|View full text |Cite
|
Sign up to set email alerts
|

Two New CuII Coordination Polymers: Studies of Topological Networks and Water Clusters

Abstract: Two new CuII coordination polymers, namely [Cu2(BDC)2(L)4(H2O)2]·14H2O (1) and [Cu1.5(BTC)(L)1.5(H2O)0.5]·2H2O (2), where L = 1,1′‐(1,4‐butanediyl)bis(imidazole), BDC = 1,4‐benzenedicarboxylate, and BTC = 1,3,5‐benzenetricarboxylate, have been synthesized at room temperature. Complex 1 exhibits an unusual, square‐planar, four‐connected 2D 264 net, which has been predicated by Wells. Interestingly, three types of water clusters, namely (H2O)6, (H2O)8, and (H2O)10, are observed in the hydrogen‐bonded layers cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…The carboxylate group of the complex show two bands, an intense asymmetric carboxylate stretching v(as, coo À ) and a symmetric stretching v(s,coo À ) at about 1622 and 1383 cm À1 , respectively, The values of Dv(coo À ) (v(as,coo À ) À v(s,coo À )) is 239 cm À1 , suggesting that the carboxylate group is amonodentate coordinated through oxygen atoms [27]. And the broad bands around 3383 cm À1 attributable to the OeH stretching frequency suggest that lattice waters exist in the complex [28]. The above speculations were consistent with the crystal structure of the title complex by X-ray analysis.…”
Section: Ir Spectral Analysesmentioning
confidence: 93%
“…The carboxylate group of the complex show two bands, an intense asymmetric carboxylate stretching v(as, coo À ) and a symmetric stretching v(s,coo À ) at about 1622 and 1383 cm À1 , respectively, The values of Dv(coo À ) (v(as,coo À ) À v(s,coo À )) is 239 cm À1 , suggesting that the carboxylate group is amonodentate coordinated through oxygen atoms [27]. And the broad bands around 3383 cm À1 attributable to the OeH stretching frequency suggest that lattice waters exist in the complex [28]. The above speculations were consistent with the crystal structure of the title complex by X-ray analysis.…”
Section: Ir Spectral Analysesmentioning
confidence: 93%
“…Semi-empirical absorption corrections were applied using the SADABS program. 21 The structures were solved by direct methods and refined on F 2 by full-matrix least squares using SHELXTL. 22 All non-hydrogen atoms were treated anisotropically.…”
Section: Notesmentioning
confidence: 99%
“…However, syntheses involving mixed ligands are more difficult due to the different solubility of mixed organic ligands and the competition between different organic ligands for the metal [20]. Numerous studies have shown that hydrothermal synthesis is a powerful method for the construction of coordination polymers from mixed ligands [21].…”
Section: Introductionmentioning
confidence: 99%